Diversity Management Competence, Inclusion Mechanisms, and Firm Performance in Southeast Asia - Djaya, Andi Amrullah; Setiawan, Lukman; SRED, Moh. Akhtar; Baharuddin, Sitti Mujahida; Azizurrohman, Muhammad (Jurnal Aplikasi Manajemen, 2026)
The rapid expansion of multicultural workforces across Southeast Asia, combined with heightened expectations of fairness and inclusion, has intensified the strategic importance of diversity management competency for organizational competitiveness. Firms across the region now face the challenge of converting diversity practices into inclusive internal conditions that support high performance. This study examines the direct influence of diversity management competency on firm performance and analyzes the mediating roles of inclusive climate, advancement opportunity, and power distribution, while also assessing the moderating role of leadership inclusiveness. A quantitative explanatory design was employed. The population consisted of employees working in medium and large organizations in Indonesia, Malaysia, Thailand, the Philippines, Vietnam, and Brunei. A proportional stratified sampling technique was used to represent multiple sectors, resulting in a final sample of 612 respondents. Data were collected over a three-month period through structured questionnaires administered both onsite and online. Structural equation modeling was used to test the proposed framework. The results show that diversity management competency improves firm performance both directly and through the three mediating mechanisms. An inclusive climate encourages open participation, advancement opportunity strengthens motivation and retention, and equitable power distribution enhances trust and collaboration. Leadership inclusiveness further amplifies these relationships by shaping perceptions of fairness and shared influence across diverse groups. This study provides significant implications for organizational leaders and policymakers in Southeast Asia. Building strong diversity management competencies, supported by inclusive climates and equitable structures, can improve employee contributions, strengthen collective resilience, and enhance long-term firm performance.